INCREASING STUDENTS’ READING COMPREHENSION BY USING JIGSAW TECHNIQUE - Ifrianti, Syofnidah (English Education: Jurnal Tadris Bahasa Inggris, 2013)
The objective of the research is to find out whether jigsaw technique can increase students‟ reading comprehension on fifth semester of English Education Program Study of Tarbiyah and Teacher Training Faculty, State Institute for Islamic Studies Raden Intan Lampung.This was a Classroom Action Research (CAR) which was conducted in twocycles. There were three meetings for each cycle. Not only teacher‟s activity, but also students‟ activity which were observed during the implementation of jigsaw technique in reading class. Finally, to know the increase of students‟ achievement the researcher used reading comprehension test. The test was given at the end of each cycle.Result of the test which was given at the end of cycle 1 showed that there were 24 students or 71% of all who got higher score and 10 students or 29% of all who got lower score. Since the target of this research had not been reached, then the research was continued to cycle 2. Result of the test which was given at the end of cycle 2 showed that there were 30 students or 88% of all who got higher score. On the contrary, only 4 students or 12% of all who got lower score. Thus, this research was stopped because the target has been reached. Thus, the conclusion of this research was: Jigsaw technique can increase students‟ reading comprehension on fifth semester of English Education Program Study of Tarbiyah and Teacher Training Faculty, State Institute for Islamic Studies Raden Intan Lampung, in academic year 2013/2014.